Predictive control of a direct series resonant converter with active output voltage compensation - Reyes-Moraga, Eduardo Felipe (2015)
Modern high power supplies are based on resonant converters in order to use high frequency reactive elements (for reduced size) without sacrificing converter efficiency. In an effort to achieve compact high power supplies, direct power converter topologies have been considered, since these are mainly characterised by their high power density. A direct resonant converter topology combines matrix converters with conventional resonant converters.